Emerging Evidence of Positive Youth Constructs and Purpose Development: Results From a Qualitative Approach. (May 2021) - Tevington, Patricia; Chauveron, Lisa M.; Urban, Jennifer Brown; Gama, Lauren; Glina, Monica; Quinn, Johanna; Linver, Miriam R.
This study investigates how adolescents begin to demonstrate skills and approaches that help them pursue their aspirations. The qualitative study examined emergent forms of key indicators of adolescent thriving: the 5Cs of positive youth development and sense of purpose. Pre- and post-program interviews with 24 S2 (~seventh grade) Scottish adolescents who participated in a school-based character program explored the presence, absence, and elucidations of each of the 5Cs as well as their conceptualizations of a sense of purpose. Findings showed great variability within the sample, despite participants' similarities in age, race, ethnicity, and socioeconomic status. This work informs future study and measurement of potentially nascent forms of the 5Cs and purpose among early adolescents.